A World of Change: A Study of Human and Climate Elements - Marinică Tiberiu Șchiopu, PhD; Dr.Hayri Uygun; Prof. Dr.Rashmi Gujrati (Zien Journals, 2022)
The present study explores the current state of our planet and society as interdependent systems and their evolution in Anthropocene and Post-Anthropocene. The current essay initiates from the actual situation of Earth and Human society and continues with the interrelated future of ecosphere and non-biotic elements, referring to historical, geographical and biological facts, as well as to climate fiction. The increasing concern of environmentalists regarding the evolution of our planet in relation to human activity represents the starting point of this article. Climate change, human migrations and their representations in world literature are other main topics of the analysis. As we can notice the present changes in the surrounding space due to anthropic activity, climate fiction offers us new perspectives of the future, possible ways in which the Earth can evolve. The analysis will make use of the methods and instruments provided by Humanities and Social Sciences and try to study different factors related to climate and humans.
Keywords: change; climate; environment; fiction